Factors influencing accounting information system usage by oil companies & performance outcomes - Ibrahim Magboul; Mohammad Jebreel; Fekri Shawtri; Majed Qabajeh; Ayman Shanti; Mohammad Alqudah; Yazan Abu Huson (Cogent Business & Management, 2024)
Information systems have greatly enhanced companies' capabilities to record, track, and measure performance. This study examines the factors influencing employees' use of accounting information systems (AISs) in Sudan's top five oil companies and investigates how these systems impact both financial and non-financial performance. Furthermore, it evaluates the effects of top management support, trust, training, technical support, and perceived ease of use on AIS usage, as well as its subsequent impact on company performance. Surveys of 215 employees collected data, and a structural equation model tested the hypotheses. The data supports three hypotheses concerning AIS usage factors. Notably, the study demonstrates that AIS usage significantly enhances both financial and non-financial performance. This article is notable for directly addressing the practical application of AISs and their impact on organisational financial and non-financial performance, highlighting the significant value of AIS implementation in the oil industry. The conclusion summarises the key findings and offers recommendations for future research in this area.
Keywords: 650; Accounting information system; usage; factors; outcomes performance; information system; Sudan